Samegården, huvudmodell - (:unkn) unknown (Chalmers tekniska högskola // Institutionen för arkitektur och samhällsbyggnadsteknik, 2026)
Samegården Kiruna is a hotel, culture centre and part museum, located near the old city centre in Kiruna/Giron. The location can be described as the north of Sweden and middle of Sápmi. In the middle of the 1900's, Kiruna was a meeting place for Sámi from neighbouring villages. They frequently travelled to Kiruna to discuss business and share knowledge and news. At this time, Sámi were not allowed or welcomed in the regular hotels, so they were forced to build a place of their own. After ten years of effort by the Sámi, Samegården was finally built in 1973. The funding came from the municipality, the County Labor Board and LKAB (the mining company). The top floor is made up of rooms for rent, and the bottom floor is reserved for meeting rooms, offices and exhibition spaces. Samegården is not an institution or a monument. It was built, and is still used, as a space for community. The main model is made to look as realistic as possible when it comes to material and colours as a way of documenting it, since Samegården is likely to be demolished in the near future. This includes, for example, the wooden panels on the upper half of the facades and the stone panels on the lower half. However, the model highlights the original and more vibrant colour palette in contrast to what it actually looks like today, since the actual building has been affected by time and weather for more than 50 years. By lifting the roof of the model, one can see the plan of the rooms on the second floor where Samegården has its main lodging for guests. The spiral staircase in the heart of the building is also painted completely red to enhance it and make it stand out as an important function and detail.
Samegården, main model
Keywords: kiruna; sámi; sápmi; indigenous; nordic architecture; hotel; culture centre; museum; exhibition; community; preservation; ornamentation; details; colour; wood; stone; concrete